Transverse optical torque from the magnetic spin angular momentum - Wen Jiquan; He Fengling; Feng Lv; Lu Wanli; Lin Zhifang; Zheng Hongxia; Chen Huajin (Nanophotonics)
We report a transverse optical torque exerted on a conventional isotropic spherical particle in a direction perpendicular to that of the illuminating wave propagation. By using full-wave simulations and deriving an analytical expression of the transverse optical torque for particle of arbitrary size, the origin of this transverse optical torque is traced exclusively to the magnetic part of the spin angular momentum, regardless of the size and composition of the illuminated particle. To our surprise, for a non-magnetic dielectric particle, the transverse optical torque is found to originate mainly from the magnetic response of the particle, even when the particle size is much smaller than the illuminating wavelength. This is contrary to the general intuition that the electric response of a non-magnetic dielectric particle dominates its magnetic response in the mechanical effect of light, especially in the Rayleigh limit.